Limited-transpiration response to high vapor pressure deficit in crop species. (July 2017) - Sinclair, Thomas R.; Devi, Jyostna; Shekoofa, Avat; Choudhary, Sunita; Sadok, Walid; Vadez, Vincent; Riar, Mandeep; Rufty, Thomas
Highlights: Limited transpiration at elevated vapor pressure deficit confers drought tolerance. Trait associated with low hydraulic conductivity in plant. Aquaporin expression related to hydraulic conductivity and limited transpiration. Genotypic variability for limited transpiration identified in major crop species. Success in basic physiological research being used in improved crops. Abstract: Water deficit under nearly all field conditions is the major constraint on plant yields. Other than empirical observations, very little progress has been made in developing crop plants in which specific physiological traits for drought are expressed. As a consequence, there was little known about under what conditions and to what extent drought impacts crop yield. However, there has been rapid progress in recent years in understanding and developing a limited-transpiration trait under elevated atmospheric vapor pressure deficit to increase plant growth and yield under water-deficit conditions. This review paper examines the physiological basis for the limited-transpiration trait as result of low plant hydraulic conductivity, which appears to be related to aquaporin activity. Methodology was developed based on aquaporin involvement to identify candidate genotypes for drought tolerance of several major crop species. Cultivars of maize and soybean are now being marketed specifically for arid conditions. Understanding the mechanism of the limited-transpiration trait has allowed a geospatial analyses to define the environments in which increased yield responses can be expected. This review highlights the challenges and approaches to finally develop physiological traits contributing directly to plant improvement for water-limited environments.